Risks of nutritional supplements consumption by pregnant women (Journal of Medical Science, 2017)
During pregnancy the demand for nutrients, energy, vitamins and minerals increases. The diet used during pregnancy and before conception should provide the best conditions for the development of young, but often it is insufficient to cover the demands for both a pregnant woman and the fetus. Therefore pregnant woman, in the case of nutritional deficiencies and inability to cover them as the part of the daily diet, is often obliged to supplement the nutrition that she and the baby need. Moreover, the deficit of the nutritional elements during this period may increase the risk of various types of disorders complicating the pregnancy and affecting the development and the health of the baby. The working scheme of medicines may be changed due to nutritional supplements through the increase of their excretion, decrease in their absorption and/or disruption of metabolism. Many adverse events can occur due to the simultaneous application of both nutrition supplements and medicinal products. Therefore, the decision of including a supplementary diet should be made very carefully and individually for every patient. The use of nutrition supplements for expectant mothers should always be consulted with a physician or a pharmacist.